2012
DOI: 10.1182/blood.v120.21.4671.4671
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 From Fish Oil Augments Gvhd Through the Enhancement of Chemotherapy Conditioning Regimen and Selective Foxp3 Depletion

Abstract: 4671 Background: Omega-3 has been reported to enhance the effects of some cancer chemotherapeutic agents and to play a role in the immune system as immunoregulator and immunosuppressant. The effect of a diet rich in omega-3 during immunosuppressed states of anticancer treatment and on bone marrow transplantation (BMT) outcome is not well known. Aims: To study the effect of omega-3 on busulfan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, the number of eosinophils from total immune cells tended to be higher in tumors of ω3‐fed mice, but the difference was not statistically significant (Figure A, right). As ω3 and ω6 FA have been shown to modulate the number and function of immunosuppressive T regulatory cells (Treg) in tumors, we also studied the tumor infiltration by natural FoxP3+ and induced IL‐10+ Treg (Tr1) cells. We found that immunosuppressive Tr1 cells were slightly but significantly more abundant in tumors of ω6‐fed mice (Figure C, left).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the number of eosinophils from total immune cells tended to be higher in tumors of ω3‐fed mice, but the difference was not statistically significant (Figure A, right). As ω3 and ω6 FA have been shown to modulate the number and function of immunosuppressive T regulatory cells (Treg) in tumors, we also studied the tumor infiltration by natural FoxP3+ and induced IL‐10+ Treg (Tr1) cells. We found that immunosuppressive Tr1 cells were slightly but significantly more abundant in tumors of ω6‐fed mice (Figure C, left).…”
Section: Resultsmentioning
confidence: 99%
“…11 The bioavailability of these drugs is correlated with several factors including age of the patient, genetic make-up, gut function, gut flora, and types of ingested food, in addition to the chemical and physical properties of the drug. 17,18 In a multicentric phase III clinical trial, low doses of cytostatics were compared to higher doses with regard to the outcome of SCT and survival. The study was permanently halted as higher doses were clearly associated with a better prognosis.…”
Section: Introductionmentioning
confidence: 99%